2013
DOI: 10.1021/ct400649r
|View full text |Cite
|
Sign up to set email alerts
|

Longest-Wavelength Electronic Excitations of Linear Cyanines: The Role of Electron Delocalization and of Approximations in Time-Dependent Density Functional Theory

Abstract: The lowest-energy/longest-wavelength electronic singlet excitation energies of linear cyanine dyes are examined, using time-dependent density functional theory (TDDFT) and selected wave function methods in comparison with literature data. Variations of the bond-length alternation obtained with different optimized structures produce small differences of the excitation energy in the limit of an infinite chain. Hybrid functionals with range-separated exchange are optimally 'tuned', which is shown to minimize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
174
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(187 citation statements)
references
References 57 publications
13
174
0
Order By: Relevance
“…For example, the meta-donor-substituted systems have an excited singlet ion diradical form that is electronically analogous to the classic meta xylylene diradical, 49 with a radical at the "carbenium center" and a cation radical donor substituent. There are numerous examples of cations that fall within this type (9,12,13,17,18,19,22,23,24,25,26,27,31). Thus, while the donor group does not act to stabilize the ground-state cation via resonance, it leads to stabilized singlet diradical excited states.…”
Section: ■ Computational Resultsmentioning
confidence: 99%
“…For example, the meta-donor-substituted systems have an excited singlet ion diradical form that is electronically analogous to the classic meta xylylene diradical, 49 with a radical at the "carbenium center" and a cation radical donor substituent. There are numerous examples of cations that fall within this type (9,12,13,17,18,19,22,23,24,25,26,27,31). Thus, while the donor group does not act to stabilize the ground-state cation via resonance, it leads to stabilized singlet diradical excited states.…”
Section: ■ Computational Resultsmentioning
confidence: 99%
“…Geometries at the MP2/cc-pVQZ level were taken from Ref. [4]. The linear cyanine molecules have C 2v symmetry, and the excitation from the ground (A 1 ) to the lowest (B 2 ) singlet state was considered.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The observation is surprising because the lowest excited-state is described as the excitation from the highest occupied molecular orbital (HOMO) to the lowest unoccupied molecular orbital (LUMO). Several benchmark studies have been reported using various methodologies including multi-reference perturbation theory, many-body perturbation theory, coupled cluster, diffusion Monte Carlo (DMC), and density functional theory [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is well-known that linear-response TD-DFT tend to overshoot the transition energies of cyanine structures (by ca. 0.20-0.60 eV) compared to accurate reference data [27,28,49,50]. Whilst the use of the most modern exchange-correlation functionals, such as M06-2X [28] or optimally-tuned range separated hybrids [50], alleviate TD-DFT's error for cyanines making the obtained absolute deviation more in the line of other states, all tested TD-DFT protocols tend, to the best of our knowledge, to provide too large transition energies for this family of dyes.…”
Section: Nature Of the Excited-states And 0-0 Energiesmentioning
confidence: 99%